EP666 Childbearing desire and pregnancy outcome in patients underwent fertility sparing surgery for Borderline Ovarian Tumours. (1st November 2019) - Candotti, G; Peiretti, M; Mangili, G; Bergamini, A; Cioffi, R; Fais, ML; Mais, V; Pella, F; Proto, A; Rabaiotti, E; Turba, F; Bocciolone, L
Abstract : Introduction/Background: Borderline ovarian tumors (BOTs) are characterized by the presence of cellular proliferation and nuclear atypia without stromal invasion. Compared to malignant ovarian tumors, BOTs typically present in younger women and have better prognoses. Considering the good prognosis of BOT, fertility-sparing surgery can be considered for young women who desire to preserve fertility. Our study evaluated the pregnancy rate in patients with childbearing desire, the efficacy and risk of recurrence of women affected by BOTs who have undergone fertility-sparing surgery. Methodology: From June 2000 to December 2017, patients with a diagnosis of BOT have been restrospectively recruited at the San Raffaele Hospital, Vita e Salute University Milan and Policlinico Monserrato, University of Cagliari. Eighty-five patients underwent fertility-sparing surgery for BOT were interviewed about child wishing and pregnancy outcomes. Patients characteristics including age at diagnosis, tumor pathological characteristics, surgical management at primary treatment and relapse, follow up data were collected. Results: Eithy-five patients were recruited for the study. Median age at diagnosis was 33 years (I.Q.R 29–38). Unilateral salpingo-oophorectomy was performed in 33 patients (38%), unilateral cystectomy in 40 (47%) and 12 underwent both procedures (14%). 40 women (50%) tried to conceive after surgery. We recorded 33 pregnancies, 8 miscarriages and 27 deliveries. 7 patients underwent ART for infertility and 5 of them obtained pregnancy The pregnancy rate was 73% and live birth rate was 67%. Childbearing desire and age at diagnosis were significantly associated with the pregnancy rate (PR). Conclusion: Conservative surgical treatment seems to be a reasonable therapeutic option for women with BOTs who wish to preserve fertility. Our results suggest that the obstetric outcomes after fertility sparing surgery are promising. Maternal desire and the age of diagnosis are the most important factors affecting PR after surgery. Fertility counselling should be an integral part of the clinical management of women with BOT. Disclosure: Nothing to disclose.